Regional variation and articulation rate in French. (January 2015) - Schwab, Sandra; Avanzi, Mathieu
Abstract: The present investigation deals with regional variation and articulation rate in French. The articulation rate in read speech and in spontaneous speech was examined in seven variants of French: Paris and Lyon in France; Tournai and Liège in Belgium; Geneva, Neuchâtel and Nyon in Switzerland. Results showed that Swiss speakers articulate at a lower syllable rate than French speakers (especially Parisian speakers) and Belgian speakers, independently of the speaking style (reading or conversation). This finding confirms that articulation rate varies regionally. Moreover, results revealed that extra-linguistic and linguistic factors, such as the speaker's age and gender, the speaking style, the utterance length and the articulation rate of the adjacent inter-pause chunk, also affect articulation rate. Highlights: Swiss speakers of French articulate slower than Standard French speakers. Belgian speakers of French articulate as fast as Standard French speakers. Belgian speakers of French articulate faster than Swiss speakers of French. Males articulate faster than females. Articulation rate decreases with age.